2009
DOI: 10.1073/pnas.0903898106
|View full text |Cite
|
Sign up to set email alerts
|

A phosphoenzyme mimic, overlapping catalytic sites and reaction coordinate motion for human NAMPT

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is highly evolved to capture nicotinamide (NAM) and replenish the nicotinamide adenine dinucleotide (NAD ؉ ) pool during ADP-ribosylation and transferase reactions. ATP-phosphorylation of an active-site histidine causes catalytic activation, increasing NAM affinity by 160,000. Crystal structures of NAMPT with catalytic site ligands identify the phosphorylation site, establish its role in catalysis, demonstrate unique overlapping ATP and phosphoribosyltransferase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 34 publications
(69 reference statements)
6
80
0
Order By: Relevance
“…This is also evident from our gene knockdown experiments, which further revealed that two other phosphoribosyltransferases, APRT and NAMPT, are irrelevant for the antiviral activity of these 2-pyrazinecarboxamide compounds. NAMPT was included because of the structural analogy between T-705 and nicotinamide (Burgos et al, 2009). These gene knockdown experiments confirmed the role for ADK in activating ribavirin (Willis et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…This is also evident from our gene knockdown experiments, which further revealed that two other phosphoribosyltransferases, APRT and NAMPT, are irrelevant for the antiviral activity of these 2-pyrazinecarboxamide compounds. NAMPT was included because of the structural analogy between T-705 and nicotinamide (Burgos et al, 2009). These gene knockdown experiments confirmed the role for ADK in activating ribavirin (Willis et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…4B) have a covalent His247·BeF3 − , though, in contrast to all other trifluoroberyllate structures, magnesium is coordinated to one fluorine without any direct linkage to His247. [8] …”
Section: Histidine Trifluoroberyllatesmentioning
confidence: 99%
“…27,28 iNampt is phosphorylated at histidine 247, resulting in a 160,000-fold increased enzymatic affinity for NAM. 29 iNampt and eNampt undergo other posttranslational modifications, including acetylation and ubiquitization. The significance of these modifications is presently poorly understood.…”
Section: Zhang Et Almentioning
confidence: 99%